Design of PCF-SPR for Early Detection of Skin Cancer Infected Cells - Dedi Irawan; Khaikal Ramadhan; Azhar Azhar (Jurnal Penelitian Pendidikan IPA, 2022)
In this work, we carried out a numerical investigation of the PCF-SPR biosensor for the early detection of infected skin cancer cells and healthy cells. The study was conducted using the COMSOL Multiphysics-based FEM method. The dielectric material used in this PCF design is fused silica, while the plasmonic material is gold. The study was conducted to test the effect of the thickness of the plasmonic layer and the size of the air hole diameter on the PCF-SPR. It was found that the larger the diameter of the air hole in the proposed sensor gives a smaller confinement loss value, while the thicker the plasmonic material used also gives a small confinement loss value. The proposed PCF-SPR has a wavelength sensitivity in detecting skin cancer-infected cells of 7000 nm/RIU. These results indicate that the proposed sensor has a good performance in detecting cells infected with skin cancer.